2017
DOI: 10.1111/ajo.12641
|View full text |Cite
|
Sign up to set email alerts
|

The use of selective progestin receptor modulators (SPRMs) and more specifically ulipristal acetate in the practice of gynaecology

Abstract: This review discusses the development of selective progestin receptor modulators (SPRMs) for use in women's health and specifically the use of ulipristal acetate (UPA) as emergency contraception (EC) and as a treatment for symptomatic fibroids in women who want to preserve their fertility or avoid a hysterectomy. As an EC, UPA 30 mg should be recommended for women, within 102 h of unprotected intercourse. As a treatment of fibroids, UPA (5 mg daily dose) should be administered for periods of three months as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…There are studies that use off-label in the treatment of endometriosis.19 When UPA (5 mg daily dose) is administered for three months before the surgery in the treatment of fibroids, it reduced vaginal bleeding and fibroid size, facilitated the operation, and helped patients (20,21). In the present study, it was shown that daily doses of 5mg and 10mg used for 3 months seem safe and effective in bleeding control (22).…”
Section: Discussionmentioning
confidence: 59%
“…There are studies that use off-label in the treatment of endometriosis.19 When UPA (5 mg daily dose) is administered for three months before the surgery in the treatment of fibroids, it reduced vaginal bleeding and fibroid size, facilitated the operation, and helped patients (20,21). In the present study, it was shown that daily doses of 5mg and 10mg used for 3 months seem safe and effective in bleeding control (22).…”
Section: Discussionmentioning
confidence: 59%
“…Initially, UPA have been used to reduce the fibroid volume for 3 months before surgery. However, recently, it is used in patients who refuse to remove their uterus ( Pazzaglia et al, 2017 ; Rozenberg et al, 2017 ). Due to the progesterone antagonist activity of UPA on the endometrium, this could cause an unopposed estrogen activity, which may increase cell proliferation.…”
Section: Drawbacks Of the Current Treatments For Uterine Fibroidsmentioning
confidence: 99%
“…Less than 6 month GnRHa is associated with limited and reversible bone loss, while GnRHa therapy for more than 6 months induces important bone loss. The current indication is severe endometriosis, before surgery or before IVF, since patients with uterine fibroids, are nowadays treated with Ulipristal acetate instead of GnRHa [115].…”
Section: Drug Inducedmentioning
confidence: 99%